2013
DOI: 10.1557/mrs.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Condensation heat transfer on superhydrophobic surfaces

Abstract: (150 words max)Condensation is a phase change phenomenon often encountered in nature and industry for applications including power generation, thermal management, desalination, and environmental control. For the past eight decades, researchers have focused on creating surfaces allowing condensed droplets to be easily removed by gravity for enhanced heat transfer performance.Recent advancements in nanofabrication have enabled increased control of surface structuring for the development of superhydrophobic surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
260
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 341 publications
(267 citation statements)
references
References 128 publications
6
260
0
1
Order By: Relevance
“…[30,[95][96][97][98][99][100] Condensation has two basic modes: filmwise condensation in the case of hydrophilic surfaces, where the condensate exists in the form of a continuous liquid film, and dropwise condensation in the case of hydrophobic surfaces, which is characterized by the dynamic self-renewal of discrete drops. [99] It has been reported that dropwise condensation results in more efficient energy transport, allowing a heat-transfer coefficient that is 5-7 times higher than that of filmwise condensation, since discrete drops have relatively lower thermal resistance than continuous liquid films and can release a larger number of bare sites for nucleation and thermal energy transport.…”
Section: Enhanced Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…[30,[95][96][97][98][99][100] Condensation has two basic modes: filmwise condensation in the case of hydrophilic surfaces, where the condensate exists in the form of a continuous liquid film, and dropwise condensation in the case of hydrophobic surfaces, which is characterized by the dynamic self-renewal of discrete drops. [99] It has been reported that dropwise condensation results in more efficient energy transport, allowing a heat-transfer coefficient that is 5-7 times higher than that of filmwise condensation, since discrete drops have relatively lower thermal resistance than continuous liquid films and can release a larger number of bare sites for nucleation and thermal energy transport.…”
Section: Enhanced Heat Transfermentioning
confidence: 99%
“…Example applications are the enhancement of condensation heat transfer for high-efficiency thermal management and energy utilization, [20][21][22][23][24][25] energy-effective antifreezing for airconditioner heat exchangers and aircraft wings, [26][27][28] and electrostatic energy harvesting. [29] In general, condensate drops on typical flat hydrophobic surfaces are only shed off under gravity when their sizes are comparable to the capillary length (≈2.7 mm for water), [30] which creates undesirable effects such as large thermal resistance [20][21][22][23][24][25] and the freezing of subcooled drops. [26][27][28] Clearly, a great challenge is the timely removal of condensate drops at the microscale where the gravitational effect does not work.…”
mentioning
confidence: 99%
“…3 These phenomena have sparked an interest in spontaneous drop detachment and lift-off, with several authors reporting similar observations on artificial substrates. The drop recoil-and-jump mechanism has been successfully exploited for enhanced heat exchange, [4][5][6][7][8] as the spontaneous jump of coalescing droplets provides an efficient way to remove liquid from a cooler surface. The same physical mechanism has been applied in single-droplet, non-coalescence based, capillary-to-inertial energy conversion by melting-initiated 9,10 and electrowetting-actuated a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main technological challenges is to create such a surface, so as to allow condensation and evacuation of the droplets to take place in a continuous manner. Droplet coalescence is a complex physical phenomenon and optimisation of kinematic conditions leading to surface dewetting and jumping of droplets is of paramount importance for processes like heat transfer, de-icing, atmospheric water harvesting or dehumidification [4][5][6]. Dropwise condensation heat transfer performance can be enhanced by allowing condensed droplets to be removed rapidly from the surface to minimize the thermal barrier [7].…”
mentioning
confidence: 99%
“…Dropwise condensation heat transfer performance can be enhanced by allowing condensed droplets to be removed rapidly from the surface to minimize the thermal barrier [7]. Recently, researchers showed that superhydrophobic surfaces provide a higher mobility of condensates, which may enhance the heat transfer performance [1][2][3][4][5][6][7]. Coalescence-induced jumping phenomena occur on superhydrophobic surfaces but within a small range of initial droplet radii.…”
mentioning
confidence: 99%